Synergetic effect of a super-absorbent polymer and a calcium nitrite corrosion inhibitor in high performance concrete durability - Duran Herrera, Alejandro; Canul-Polanco, Jennifer Anette; Dávila-Pompermayer, Rogelio; López-Yépez , Lucio Guillermo; Valdez-Tamez , Pedro Leobardo (Revista ALCONPAT, 2020)
In this research, the synergetic effect of a super-absorbent polymer in combination with a calcium nitrite corrosion inhibitor were evaluated as a combined technology to improve concrete durability in High Performance Concrete. For this purpose, Portland cement mortars with a water/cement ratio of 0.4 and a substitution of 9.5% of cement by silica fume were produced. The effect of this technologies was evaluated by measuring the following parameters: autogenous and drying shrinkage, surface electrical resistivity and the non-steady-state chloride migration coefficient. The results indicate that the synergistic effect of SAP + CNI improves autogenous shrinkage and surface electrical resistivity.